PENGARUH DISKUSI KELOMPOK TERHADAP PENGETAHUAN MENGGOSOK GIGI SISWA SD DALAM PENERAPAN PHBS - Jansen Parlaungan; Panel Situmorang; Waode Suriani (Jurusan Keperawatan Poltekkes Kemenkes Sorong, 2020)
ABSTRACT Introduction: The ability to brush your teeth properly and correctly is an important factor for oral health care. Objective: Knowing the knowledge of how to brush the teeth of the fifth grade students of SD YPK Klasaman II, Sorong City, West Papua after the intervention of the group discussion method. Methods: This type of research is a semi-experimental research (Quasi Experiment) with a non-randomized control group pretest-posttest design. The sample of class V SD YPK Class II Sorong City, West Papua is 60 students. Results: The study showed that there were differences in knowledge of how to brush teeth between before and after receiving the intervention group discussion method in the experimental group. It can be seen that the p value (t test) = 0.000 <0.05. There were differences in the post-test knowledge of how to brush teeth in the control group and the experimental group. It can be seen that the p-test value t = 0.004 <0.05. Conclusion: It can be used by schools in order to create school programs related to increasing knowledge about health, especially in the knowledge of brushing teeth, one of which is by holding health education in collaboration with health education institutions such as the Poltekkes Kemenkes Sorong. Keywords: Knowledge; Group Discussion; Brushing Teeth.